Challenges faced by the visually disabled in use of medication, consequences of medication errors and their self-adopted coping strategies at a tertiary care hospital in Goa, India - Naik, Mrudul; Cacodcar, Jagadish A.; Dhupdale, Nitin Y. (International Journal Of Community Medicine And Public Health, 2018)
Background: Visual impairment (VI) does limit individual’s ability to complete everyday tasks and impact their quality of life and ability to interact with their environment. The objectives of this study are to determine challenges faced by people with Visually Disability, medicine administration errors and self-adopted coping strategies. Methods: An observational case series study design was used for the data collection. The data was collected from January-June 2014. The study participants were included all patients more than 18 years who were certified as visually handicap. Results: The major challenges faced by total 146 visually disabled patients studied were, 51.36% couldn’t locate the place of medication and 45.89% couldn’t identify the separate containers of medications. The major Medications errors included of 30.13% study participants had missed doses and spilled medications. The most commonly used coping measures were keeping medications at specific places, identifying separate drugs by feeling the shape of the container. Conclusions: The challenges included, inability to locate the place of medication, inability to identify the separate containers of medications, unaware of correct dose, inability to maintain dose schedule and difficulty in using liquid medications. Medication errors included, missing doses, spillage of medications, consumption of wrong medication, wrong dosage, inability to complete course of prescribed medications. The coping strategies adopted included, keeping medications at specific places, identifying separate drugs by feeling the shape of the container, tracking the time of routine medications with the timings of the TV serials/shows.